An in situ transmission electron microscopy study of the ion irradiation induced amorphisation of silicon by He and Xe. (1st March 2016) - Edmondson, P.D.; Abrams, K.J.; Hinks, J.A.; Greaves, G.; Pawley, C.J.; Hanif, I.; Donnelly, S.E.
Abstract: Transmission electron microscopy with in situ ion irradiation has been used to examine the ion-beam-induced amorphisation of crystalline silicon under irradiation with light (He) and heavy (Xe) ions at room temperature. Analysis of the electron diffraction data reveal the heterogeneous amorphisation mechanism to be dominant in both cases. The differences in the amorphisation curves are discussed in terms of intra-cascade dynamic recovery, and the role of electronic and nuclear loss mechanisms. Graphical abstract: